"Working Women Unite": Exploring a Socialist Feminist, Nonhierarchical Teachers Union. (March 2020) - Massie, Alicia; Ho, Yi Chien Jade
In this paper, we present and explore the case of the Teaching Support Staff Union (TSSU), an independent, directly democratic, and feminist labor union at Simon Fraser University in British Columbia, Canada. Operating continuously since the 1970s, we argue that TSSU is an important example of the ways in which gender and class have intersected within the history of the Canadian labor movement, and a fascinating case of a longstanding socialist feminist union. We also argue that alongside the historical relevance, exploring the constraints and possibilities of a feminist nonhierarchical organizational structure can offer important lessons for organizing in the twenty-first century. Adopting a socialist feminist framework, we speak from our experiences serving as TSSU executives, as graduate students, and as teachers within the larger academic machine. Marking its fortieth year in 2018, this active, young, and angry labor union can provide the labor movement and academics with a case study to reflect on how we can conceptualize social movement unionism; organize around and toward equity, diversity, and justice; and maintain a deep commitment to both feminist and class struggle.